PROGRAM PENGEMBANGAN PRODUKSI BEBEK PEDAGING DAN PETELUR DI DESA PEDALEMAN KECAMATAN TANARA - Ombi Romli; Arta Rusidarma Putra; Rizwar Munfaridz (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Pedaleman Village, Tanara District, is an area with great potential, especially in the Peking duck breeding sector, reaching more than 3,250 heads. The partner in this PKM activity was Juan Faisal as a member of the Peking duck livestock group in Pedaleman Village, Tanara District. Temporary observation of partners that there are deficiencies in Peking duck farming, such as difficulties in obtaining superior seeds, high costs of animal feed, sales and traditional handling of hatching eggs. This problem must be found the right solution so that the welfare of the community (partners) will increase through development and improvement programs in terms of technology for egg hatching machines and animal feed machines. The introduction of egg incubators and Peking duck feed making machines is an alternative solution to existing problems. The methods in this PKM are: (a) Extension of quality duck livestock, (b) Training and use of technology, (c) Utilization of renewable feed which is more economical (d) As well as business management training. The results achieved are: (a) Partners are able to produce quality seeds independently, (b) Partners are able to operate egg "incubator" technology and "feed making machine", (c) Partners are able to reduce Peking duck feed costs and increase livestock productivity (d) Partners are able to sell and get maximum profit and are able to make good financial reports